The Influence of Electrochromic Film on Indoor Environmental Quality - Kuan-Ting Yeh; Wei-Chieh Hu; Chun-Kuei Chen; Ta-Hui Lin; Feng-Yi Lin; Chung-Chih Cheng; Tzu-Ching Su; Pei-Yu Yu (Energies)
This study was conducted at SPINLab. The full-scale experiments were performed using two experimental spaces of identical specifications to investigate the effects of electrochromic film (OG + ECON or OG + ECOFF) on indoor environment and air conditioning electricity consumption in buildings with different orientations (East and West). The electricity-saving effects are more pronounced on the building’s west-facing side than on its east-facing side. For the east-facing side, the average electricity savings for OG + ECON and OG + ECOFF were 4.5%, and 5.1%, respectively. For the west-facing side, the average electricity savings increased to 9.2% and 9.4% for OG + ECON and OG + ECOFF. The research results on thermal comfort indicate (PMV) that applying electrochromic film (OG + ECON or OG + ECOFF) significantly improved indoor thermal comfort compared to using clear glass (OG) alone. The visual comfort analysis results indicate that the opaque (OG + ECOFF) and transparent (OG + ECON) states of electrochromic film could reduce daylight glare probability (DGP) values. However, due to the light-scattering properties of the liquid crystal droplets, the OG + ECOFF and OG + ECON states of the electrochromic film increased DGP values in 26.5% and 41.5% of the cases, respectively, when sunlight directly entered the interior.